Microstructure, Property and Processing of Functional Ceramics - Yin, Qingrui; Zhu, Binghe; Zeng, Huarong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Microstructure, Property and Processing of Functional Ceramics describes the preparation, property and local structure microscopy of functional ceramics. It covers functional ceramic fabrication processing, grain boundary phenomena and micro-, nanoscale structures characterizations including scanning electron acoustic microscopy, scanning probe acoustic microscopy and piezoresponse force microscopy. This book is intended for advanced undergraduates, graduates and researchers in the field of materials science, microelectronics, optoelectronics and microscopy. Qingrui Yin and Binghe Zhu both are professors at the Shanghai Institute of Ceramics, Chinese Academy of Sciences; Dr. Huarong Zeng is an associate professor at the Shanghai Institute of Ceramics, Chinese Academy of Sciences.
Microstructure and Properties of Functional Ceramics -- Grain Boundary Phenomena of Functional Ceramics -- Near-field Acoustic Microscopy of Functional Ceramics -- Piezoresponse Force Microscopy of Functional Ceramics -- Fabrication Processes for Functional Ceramics -- Review and Prospect of Functional Ceramics.
Keywords: Chemical engineering; Materials; Materials Science; Materials Science, general; Industrial Chemistry/Chemical Engineering; Metallic Materials